Names of Traditional Ware and Utensils in the Yakut and Khakass Languages: Literary-Normative and Dialectal Parallels - Egor R. Nikolaev (Polylinguality and Transcultural Practices, 2022)
The aim of this article is to identify lexical-semantic parallels in the names of traditional utensils in the Yakut and Khakass languages on the basis of lexicographic material. The main objectives of the research are: to identify Khakass and Yakut names of traditional tableware and utensils; to determine the semantic features of similar lexemes; to establish literary-normative and dialectal meanings. Bilingual, explanatory, and dialectological dictionaries of the Khakass and Yakut languages were used as the research material. The methods of this study are: generalization, systematization, comparative and comparative analysis. The lexical parallels in the group of names of dairy (koumiss) utensils and utensils are revealed. The principles of motivation of the names with the bases bysh- , pys- , bul- , pool- have been established: the process of preparation of a dairy dish (product) - stirring, mixing, churning; functional characteristics - moving (Yakut verb tas- , Khakass verb tazy- ‘tug, move’). By the example of the Khakassian names ( khamys , tazor , algai ) the dialectal zone of the Yakut lexemes is determined - it is the Akakaya dialectal zone of the Yakut language. The expansion of semantics in the Yakut names kүөrčekh ( kүөččekh ) ‘mutovka’ = kүөččekh ‘whipped cream’ is revealed, sүүmächtää ‘to strain sour milk to separate the guts’ = sүүmäch ‘cream in curdled milk, curd’. The most YakutHakassian parallels are in the normative-literary layer of the lexicon. There are dialectal words from the dialects of the Khakass language (Sagai and Kachin). The dialectal units of the Yakut language represent the central, Vilyui and northeastern zones of accents.